Analisis Efektivitas Dan Kontribusi Pajak Restoran Terhadap Pendapatan Asli Daerah (Pad) Kabupaten Semarang - Giffiany Fibri Setiawan; Christiana Retno Gayatrie (Politeknik Negeri Semarang, 2018)
The final project is aimed to understand the influence of restaurant tax on local generated revenue (PAD) in Semarang Regency in 2012-2016. Locally generated revenue is one indicator to determined the local government’s autonomy level. Local tax in Semarang Regency increase from year to year. This research is conducted in Badan Keuangan Daerah Kabupaten Semarang. The method used in this final project is the analysis of effectiveness and contribution of restaurant tax in locally generated revenues as well as a simple regression analysis and simple correlation analysis to find out whether there is relationship between these variables is coincidental or indeed a truly relationship. The results of the analysis suggest that the level of effectiveness of the restaurant tax is very effective and the contribution to the restaurant tax revenue in 2012 is Rp1.717.123.699 ,in 2013 is Rp2.624.555.733 ,in 2014 is Rp3.142.559.312 in 2015 is Rp4.289.087.988 and in 2016 is Rp6.408.249.069 The relationship between restaurant tax and locally generated revenue is positive meaning that increasing the amount of restaurant tax revenue will result increased revenue.